Pelindungan Data Pribadi Anak di TikTok : Kajian Hukum terhadap Penggunaan Media Sosial oleh Pengguna di Bawah Umur - Fika Nurmajulia Andiani; Sidi Ahyar Wiraguna (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The rapid development of digital technology has changed people's lifestyles, including children as active users of the internet. However, behind these benefits, there are threats to children's privacy, especially in the context of misuse of personal data by digital platforms. This research aims to examine the effectiveness of Law Number 27 of 2022 concerning Personal Data Protection in ensuring the security of children's data on the TikTok platform. Using a normative legal approach, this study analyzes legislative provisions and legal principles related to the protection of child data. The results of the study show that although child data has been recognized as specific data that requires special protection, implementation in the field still faces various obstacles. Among them are weak age verification, lack of clarity of jurisdiction, low platform transparency, and the lack of technical implementing regulations. These challenges weaken the legal supervision of global platform organizers such as TikTok. Therefore, a derivative policy is needed that clarifies the mechanism of child data protection as well as the establishment of an independent supervisory authority. This research is expected to contribute in strengthening awareness of the importance of children's privacy rights in the digital era.